1997
DOI: 10.1002/hep.510250235
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Duck Hepatitis B Virus in Bile Duct Epithelial Cells: Implications for Pathogenesis and Persistent Infection

Abstract: ogy, genomic organization, and replication by means of reHepatitis B virus (HBV) has been demonstrated in bile verse transcription. 1,3 duct epithelial cells (BDEC) during chronic infection.The replication of human HBV has been extensively studThe persistence of virus in BDEC may play an important ied in hepatocytes, but comparatively less is known about role in disease pathogenesis, and may be at least partly HBV infection of nonparenchymal cells within the liver. Hepresponsible for the relapse phenomenon obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Using immunohistochemical and in situ DNA hybridization techniques, it was found that treatment with PMEA reduced viral protein and DNA loads in bile duct epithelial cells (BDEC) as well as hepatocytes (30). This observation is significant because the reservoir of DHBV in BDEC is refractory to treatment with nucleoside analogs such as PCV and 3TC, presumably because BDEC lack the enzymatic machinery required for their uptake or phosphorylation (29,30). Since it is a dAMP analog, PMEA is able to bypass the initial phosphorylation site, which is critical and often limiting for the activity of most nucleoside analogs (32,33) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using immunohistochemical and in situ DNA hybridization techniques, it was found that treatment with PMEA reduced viral protein and DNA loads in bile duct epithelial cells (BDEC) as well as hepatocytes (30). This observation is significant because the reservoir of DHBV in BDEC is refractory to treatment with nucleoside analogs such as PCV and 3TC, presumably because BDEC lack the enzymatic machinery required for their uptake or phosphorylation (29,30). Since it is a dAMP analog, PMEA is able to bypass the initial phosphorylation site, which is critical and often limiting for the activity of most nucleoside analogs (32,33) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Viremia was monitored by serum dot blot hybridization as previously described (7). Primary hepatocytes were obtained from livers of 7-to 14-day-old congenitally infected or virus-free ducklings and seeded into 12-well plastic culture plates (ICN Biomedicals, Aurora, Ohio) at a density of approximately 0.75 ϫ 10 6 to 1.0 ϫ 10 6 PDH per well (7,29). PDH were allowed to attach overnight before the first medium change (on day 1 postplating) and were maintained at 37°C in a humidified incubator under 5% CO 2 with medium changes every second day (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocytes are the only confirmed site of replication for all members of this virus family. Bile ductule epithelial cells may also be a target of infection, as may a subset of cells in the pancreas, kidneys, and lymphoid system (16,74,77,98,111,122,151,160,170,187,243). However, the evidence for replication of the orthohepadnaviruses in bile ductules and at extrahepatic sites is in some cases controversial or incomplete, and these sites are not usually considered in discussions of viral reproduction and pathogenesis.…”
Section: The Liver As a Target For Hepadnavirus Infectionmentioning
confidence: 99%
“…Relapse occurs in the majority of patients after therapy. The main reason is that HBV covalently closed circular DNA (cccDNA) in infected hepatocytes cannot be eliminated by antiviral agents, leading to rebound of HBV DNA after antiviral therapy [18] . The life cycle of HBV relies on a covalently closed circular form of the viral genome, which provides the template for viral pregenomic messenger RNA.…”
Section: Discussionmentioning
confidence: 99%